A numerical study of shear-induced evolutions of geometric and hydraulic properties of self-affine rough-walled rock fractures. (March 2020) - Liu, Richeng; Huang, Na; Jiang, Yujing; Jing, Hongwen; Yu, Liyuan
Abstract: Understanding the nonlinear flow regime of fluids through rock fractures is very important for accurately predicting the permeability of fractured rock masses. This study numerically generated rough fracture surfaces using the modified successive random addition algorithm and simulated fluid flow through void spaces induced by shear by solving the Navior-Stokes equations. The evolutions of geometric and hydraulic properties of 3D rough fractures during the whole shearing process are analyzed. The results show that both the asperity height and the aperture induced by shear follow Gaussian distributions. With the increments of shear displacement and/or surface roughness of fractures, both the mean aperture and standard deviation of aperture increase following exponential functions. When the shear displacement is small (i.e., 3 mm), the streamlines are very tortuous bypassing the contacts, showing obvious channeling flow phenomenon due to the small mean aperture and a large number of contacts. The critical Reynolds number increases versus shear displacement with a gradually decreasing rate. The rougher surface of fractures represented by a smaller Hurst exponent gives rise to a larger critical Reynolds number. The streamline distributions indicate that the flow anisotropy at a smaller shear displacement is more significant than that at a larger shear displacement. The permeability in the direction perpendicular to shear direction is always larger than that parallel to shear direction. This is reasonable because during shearing, the upper surface contacts the lower surface on the up slope of the asperities, which blocks the fluid flow along the direction parallel to shear direction; however, the void spaces induced by shear on the down slope provides available flow paths, enhancing the permeability in the direction perpendicular to shear direction.